PS 07-09 EFFECT OF RESVERATROL AS AN ARGINASE INHIBITOR ON VASCULAR SMOOTH MUSCLE CELL PROLIFERATION INDUCED BY NATIVE LOW-DENSITY LIPOPROTEIN. (September 2016) - Nguyen, Trieu Dieu Linh; Ryoo, Sungwoo; Choi, Hyoungtae
Abstract : Objective: Native low-density lipoprotein (nLDL) promotes vascular smooth muscle cell (VSMC) proliferation by mitogenic factors associated with hyperlipidemia. Arginase, which catalyzes the hydrolysis of arginine to ornithine and urea, plays an important role in smooth muscle cells proliferation. Further, resveratrol is a phytoalexin polyphenol that was known for possibility to prevent cardiovascular diseases. We study the mechanisms by which arginase inhibition by resveratrol improve vascular system. Design and Method: Rat smooth muscle cells (RASMCs) were treated with resveratrol prior to induction by nLDL. Mitochondrial and cytosolic calcium level was measured by fluorescent stainings. Cell proliferation was assessed by WST-1 and BrdU assays. Protein expression was analysed by Western blot. Results: nLDL increases RASMC mitochondrial and decreases cytosolic calcium level, down-regulates Calcium/Calmodulin-dependent protein kinase II (CaMKII, a regulator of vascular smooth muscle cell proliferation and remodeling), hence, induces cell proliferation. Resveratrol as an arginase inhibitor reverses the effects of nLDL on RASMC. Resveratrol treated alone as well as prior to nLDL decreases RASMC mitochondrial and increases cytosolic calcium level. Western blot analysis shows that the expression of CaMKII is increased with resveratrol treatment, and decreased when resveratrol pre-treat with nLDL, but higher than that of nLDL induction. Also, resveratrol, reduces cell proliferation, reverses the effect of nLDL. Conclusions: This study shows that resveratrol, acts as arginase inhibitor, regulates intracellular calcium level; hence, inhibits nLDL-induced proliferation in VSMC.